Thermotolerance responses in ripening berries of vitis vinifera l. cv muscat hamburg - Carbonell-Bejerano, Pablo (2013)
Berry organoleptic properties are highly influenced by ripening environmental conditions. In this study, we used grapevine fruiting cuttings to follow berry ripening under different controlled conditions of temperature and irradiation intensity. Berries ripened at higher temperatures showed reduced anthocyanin accumulation and hastened ripening, leading to a characteristic drop in malic acid and total acidity. The GrapeGen GeneChip combined with a newly developed GrapeGen 12Xv1 MapMan version were utilized for the functional analysis of berry transcriptomic differences after 2 week treatments from veraison onset. These analyses revealed the establishment of a thermotolerance response in berries under high temperatures marked by the induction of heat shock protein (HSP) chaperones and the repression of transmembrane transporter-encoding transcripts. The thermotolerance response was coincident with up-regulation of ERF subfamily transcription factors and increased ABA levels, suggesting their participation in the maintenance of the acclimation response. Lower expression of amino acid transporter-encoding transcripts at high temperature correlated with balanced amino acid content, suggesting a transcriptional compensation of temperature effects on protein and membrane stability to allow for completion of berry ripening. In contrast, the lower accumulation of anthocyanins and higher malate metabolization measured under high temperature might partly result from imbalance in the expression and function of their specific transmembrane transporters and expression changes in genes involved in their metabolic pathways. These results open up new views to improve our understanding of berry ripening under high temperatures.